Laser modified composite lithium metal battery negative electrode material and preparation method thereof

By constructing nanolithium-philic layers and decorative high-entropy alloy nanoparticles on copper foam (CF) of lithium metal batteries, and using external magnetic fields, the problem of lithium ion deposition inhomogeneity is solved, and the energy density and capacity retention rate of the battery are improved. .

CN119419208APending Publication Date: 2025-02-11DALIAN UNIV

Patent Information

Application Number
CN202411541039.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In existing lithium metal batteries, there is unevenness in the nucleation and deposition of lithium ions on foamed copper (CF), resulting in the growth of lithium dendrites and the reduction of battery energy density.

Method used

By constructing a nanolithium-philic layer on three-dimensional foamed copper (CF), and decorating high-entropy alloy nanoparticles, combined with an external magnetic field, it promotes uniform deposition and deep storage of lithium ions.

Benefits of technology

The uniform nucleation and growth of lithium ions is achieved, the energy density and capacity retention rate of the battery are improved, capacity fluctuations are slowed, and the growth of lithium dendrites is inhibited.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419208A_ABST
    Figure CN119419208A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium metal batteries, and discloses a laser modified composite lithium metal battery negative electrode material and a preparation method thereof.The preparation method comprises the steps that various weighed chloride salts are mixed in ethyl alcohol respectively, and an ethyl alcohol precursor solution with the metal element concentration being 0.01 mol / L is finally obtained through mixing; the foamy copper is subjected to ultrasonic cleaning with acetone, absolute ethyl alcohol and ultrapure water in sequence and is subjected to vacuum drying for 4-8 h at the room temperature for standby application; the prepared precursor solution is directly dropped into foamy copper with the loading capacity of 1-2 mL / cm <-2 >, and then the foamy copper is transferred into a vacuum oven and dried for 8-12 h at the room temperature; and carrying out liquid-phase laser scanning ablation on the dried foamy copper precursor to prepare the L-CF (at) HEAs sample. The liquid-phase laser technology is adopted for laser irradiation, the method is simple and good in repeatable operability, a large amount of time can be saved, the manufacturing efficiency of the lithium metal battery is improved, and the method plays an important role in promoting the development of the lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] The invention belongs to the technical field of lithium metal batteries and relates to a laser-modified composite lithium metal battery negative electrode material and a preparation method thereof. Technical Field

[0002] Metal is a substance with properties such as ductility, electrical conductivity and thermal conductivity, so it has been widely studied. The alloys formed by lithium and various metals are usually reversible, so in theory, these Li-M alloy materials can be used as negative electrodes for lithium metal batteries. Replacing metallic lithium with lithium alloys can reduce the reactivity between the anode and the electrolyte and stabilize the electrode / electrolyte interface. At the same time, the three-dimensional structure of lithium alloys can be used to provide more lithium metal storage sites, thereby inhibiting the growth of lithium dendrites.

[0003] Among the materials used as lithium-free anodes, 3D structured materials, especially copper foam (CF) with high conductivity and good mechanical properties, are generally favored. During the initial charging process, the nucleation and deposition of lithium on CF have higher energy barriers than other lithium-philic metals, resulting in Li + Ions tend to accumulate on the surface of CF rather than inside, leading to the growth of lithium dendrites and low utilization of the large space inside CF, thereby reducing the energy density of the battery. Introducing an "external strategy", such as an additional magnetic field, may be a new way to guide lithium deep into the current collector. For metal lithium batteries, similar to the micro-electroforming process, lithium ions will continuously migrate into the substrate during deposition. The introduction of a magnetic field in the battery can cause multiple magnetohydrodynamic phenomena (MHD) to occur uniformly in the battery. The electrolyte around the CF will be stirred by the MHD effect, resulting in circular motion in the microspace to enhance mass transfer, ultimately promoting Li in the substrate. + ions. Through the action of an external magnetic field, the high specific surface area of ​​CF is fully utilized to achieve full utilization of the deep lithium storage capacity, and to a certain extent, the huge capacity fluctuation is slowed down, and the generation of lithium ions in the battery is suppressed. In addition, smaller ferromagnetic particles, such as Fe-Co-Ni magnetic materials, have a better ability to provide a stronger driving force in the presence of an external magnetic source. Therefore, the superposition of magnetic field and ferromagnetic particles more effectively accelerates the Li + ions, leading to dense deposition of lithium within the CF. Similarly, the introduction of lithiophilic materials, combined with lithiophilic layers and ferromagnetic particles on 3D CF will allow Li + Ions can more easily penetrate into the interior of the frame, resulting in deep lithium deposition and higher battery capacity. The distribution of lithium materials in existing technologies is not uniform. Summary of the invention

[0004] The present invention mainly uses a liquid phase laser scanning ablation method to create an oxygen-free environment. Compared with a gas phase environment, it reduces the element loss caused by vapor pressure, efficiently completes the synthesis of high entropy alloy nanoparticles (HEANPs) with thermodynamically prohibited components and uniform element distribution in the Hume-Rothery law, and loads them on the surface of a lithium-hating three-dimensional foam copper skeleton, completes the uniform distribution of nano alloy particles including magnetic metal elements and lithium-philic metal elements, provides a large number of active sites for Li, and the superposition of magnetic elements and magnetic fields accelerates Li + The movement of ions guides the dense deposition of lithium in copper foam (CF).

[0005] The purpose of the present invention is to propose a laser-modified composite lithium metal negative electrode material in response to the background technology. By constructing a nano-lithiophilic layer on a three-dimensional skeleton copper foam (CF) to induce uniform lithium deposition, some metals are decorated on the 3D copper foam substrate as lithium active sites, so that the three-dimensional skeleton material can give full play to its advantages. The interconnected pores inside can prevent the volume deformation of the lithium metal negative electrode, and the high entropy alloy (FeCoCrInAu) nanoparticles on the skeleton surface can improve the lithium-phobic surface of the three-dimensional skeleton material and induce uniform lithium nucleation and growth.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a laser-modified composite lithium metal battery negative electrode material comprises the following steps:

[0008] Step 1, various chloride salts (HAuCl4, FeCl3, CoCl2, NiCl2, CrCl3) are mixed in ethanol respectively, and the mixture is mixed together to finally obtain an ethanol precursor solution with a metal element concentration of 0.01 mol / L;

[0009] Step 2: The copper foam was ultrasonically cleaned with acetone, anhydrous ethanol, and ultrapure water in turn and dried under vacuum at room temperature for 4-8 hours for later use; the prepared precursor solution was heated to 1-2 mL / cm -2 The loading amount was directly dropped into the copper foam, and then the copper foam was transferred to a vacuum oven and dried at room temperature for 8-12h;

[0010] Step 3: Prepare L-CF@HEAs samples by liquid phase laser scanning ablation of the dried foam copper precursor.

[0011] Compared with the existing technology, the present invention has the following beneficial effects:

[0012] (1) A nanolithiophilic layer was constructed on a 3D skeleton copper foam (CF) to induce uniform lithium deposition. To further explore the Li deposition / stripping behavior on different current collectors, the Li nanostructures were prepared at a current density of 0.5 mA cm -2 Different amounts of Li were deposited onto CF and L-CF@HEAs at 0.5 V and stripped at 0.5 V. Some metals were used as lithium active sites. The excellent electrochemical performance of the L-CF@HEAs electrode can be attributed to the fact that the abundant pores inside it alleviate the volume expansion of the negative electrode, the lithium-philic high entropy alloy provides abundant active sites during the cycle, and actively regulates the nucleation and growth of Li. Decorated on a 3D copper foam substrate, the nucleation barrier of Li is effectively reduced, allowing the three-dimensional skeleton material to give full play to its advantages and effectively prevent the volume deformation of the lithium metal negative electrode. The high entropy alloy (FeCoCrInAu) nanoparticles on the surface of the skeleton can improve the lithium-phobic surface of the three-dimensional skeleton material. At the same time, the superposition of magnetic elements and magnetic fields will accelerate Li + The movement of ions induces uniform lithium nucleation and growth.

[0013] (2) A three-dimensional lithium-philic negative electrode uniformly loaded with nano high-entropy alloy particles is designed by liquid phase laser scanning ablation for lithium metal batteries. The present invention uses liquid phase laser technology for laser irradiation. This method is simple, has good repeatability, can save a lot of time, and improves its production efficiency, which has an important role in promoting the development of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The SEM image of the present invention is a scanning electron microscope image of the original foam copper, from which it can be seen that its surface is relatively neat and smooth;

[0015] Figure 2 Schematic diagram of the contact angle of the high entropy alloy of the present invention. The contact angle between the high entropy alloy and the electrolyte is 2.5 degrees, which improves the wettability of the electrolyte. DETAILED DESCRIPTION

[0016] The present invention is described in detail below in conjunction with specific examples, which should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. Unless otherwise specified, the experimental equipment, materials, reagents, etc. used in the present invention can be obtained from commercial sources.

[0017] Example 1

[0018] Step 1: Mix the weighed chloride salts HAuCl4, FeCl3, CoCl2, NiCl2, and CrCl3 in ethanol to obtain an ethanol precursor solution with a metal element concentration of 0.01 mol / L.

[0019] Step 2: First, the commercial copper foam was ultrasonically cleaned with acetone, anhydrous ethanol, and ultrapure water in sequence and vacuum dried for later use. -2 The loading amount was directly dropped into the copper foam, and then the copper foam was transferred to a vacuum oven and dried at room temperature.

[0020] Step 3: Place the dried copper foam precursor substrate at the bottom of a beaker filled with n-hexane solution, 10 mm below the surface of n-hexane, and repeatedly scan the copper foam precursor substrate 10 times along the XY direction with a 1064 nm pulsed laser. Take out the substrate and rinse it with anhydrous ethanol to remove residual Cl. Finally, the sample is obtained after vacuum drying at room temperature. The parameters of the laser processing process are: laser frequency 20 KHz, scanning speed 600 mm / s, spot diameter 30 μm, galvanometer focal length 11.8 mm, average power 2 W. The substrate was scanned for several cycles with a pulsed laser.

[0021] Example 2

[0022] Step 1: Mix the weighed chloride salts HAuCl4, FeCl3, CoCl2, NiCl2, and CrCl3 in ethanol to obtain an ethanol precursor solution with a metal element concentration of 0.01 mol / L.

[0023] Step 2: First, the commercial copper foam was ultrasonically cleaned with acetone, anhydrous ethanol, and ultrapure water in sequence and vacuum dried for later use. -2 The loading amount was directly dropped into the copper foam, and then the copper foam was transferred to a vacuum oven and dried at room temperature.

[0024] Step 3: Place the dried copper foam precursor substrate at the bottom of a beaker filled with n-hexane solution, 10 mm below the surface of n-hexane, and repeatedly scan the copper foam precursor substrate 10 times along the XY direction with a 1064 nm pulsed laser. Take out the substrate and rinse it with anhydrous ethanol to remove residual Cl. Finally, the sample is obtained after vacuum drying at room temperature. The parameters of the laser processing process are: laser frequency 20 KHz, scanning speed 600 mm / s, spot diameter 30 μm, galvanometer focal length 11.8 mm, average power 2 W. The substrate was scanned for several cycles with a pulsed laser.

[0025] Example 3

[0026] Step 1: Mix the weighed chloride salts HAuCl4, FeCl3, CoCl2, NiCl2, and CrCl3 in ethanol to obtain an ethanol precursor solution with a metal element concentration of 0.01 mol / L.

[0027] Step 2: First, the commercial copper foam was ultrasonically cleaned with acetone, anhydrous ethanol, and ultrapure water in sequence and vacuum dried for later use. -2 The loading amount was directly dropped into the copper foam, and then the copper foam was transferred to a vacuum oven and dried at room temperature.

[0028] Step 3: Place the dried copper foam precursor substrate at the bottom of a beaker filled with n-hexane solution, 10 mm below the surface of n-hexane, and repeatedly scan the copper foam precursor substrate 10 times along the XY direction with a 1064 nm pulsed laser. Take out the substrate and rinse it with anhydrous ethanol to remove residual Cl. Finally, the sample is obtained after vacuum drying at room temperature. The parameters of the laser processing process are: laser frequency 20 KHz, scanning speed 600 mm / s, spot diameter 30 μm, galvanometer focal length 11.8 mm, average power 2 W. The substrate was scanned for several cycles with a pulsed laser.

[0029] Example 4

[0030] Step 1: Mix the weighed chloride salts HAuCl4, FeCl3, CoCl2, NiCl2, and CrCl3 in ethanol to obtain an ethanol precursor solution with a metal element concentration of 0.01 mol / L.

[0031] Step 2: First, the commercial copper foam was ultrasonically cleaned with acetone, anhydrous ethanol, and ultrapure water in sequence and vacuum dried for later use. -2 The loading amount was directly dropped into the copper foam, and then the copper foam was transferred to a vacuum oven and dried at room temperature.

[0032] Step 3: Place the dried copper foam precursor substrate at the bottom of a beaker filled with n-hexane solution, 10 mm below the surface of n-hexane, and repeatedly scan the copper foam precursor substrate 10 times along the XY direction with a 1064 nm pulsed laser. Take out the substrate and rinse it with anhydrous ethanol to remove residual Cl. Finally, the sample is obtained after vacuum drying at room temperature. Adjust the laser parameters. The parameters of the laser processing process are: laser frequency 20KHz, scanning speed 500mm / s, spot diameter 30μm, galvanometer focal length 11.8mm, average power 5W. The substrate was scanned for several cycles with a pulsed laser.

[0033] The best implementation effect is Example 4. Under this laser parameter, these metal nanoparticles are used as three-dimensional lithiophilic negative electrodes uniformly loaded with high-entropy alloy nanoparticles for lithium metal batteries. The LFPL-CF@HEAs@Li full battery shows excellent rate capability and strong capacity retention rate. At 10C, it can still achieve more than 1500 cycles, and the coulombic efficiency is stable at 99.9%.

[0034] The above-described embodiments are only preferred embodiments of the present invention, but not all feasible embodiments of the present invention. For those skilled in the art, any obvious changes made thereto without departing from the principles and spirit of the present invention should be considered to be included in the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a laser-modified composite lithium metal battery negative electrode material, characterized in that: The following steps are involved: Step 1, mixing various chloride salts weighed in ethanol respectively to obtain an ethanol precursor solution containing metal elements; Step 2, the copper foam is ultrasonically cleaned with acetone, anhydrous ethanol, and ultrapure water in sequence and vacuum dried at room temperature for later use; the prepared precursor solution is directly dropped into the copper foam, and then the copper foam is transferred to a vacuum oven and dried at room temperature; Step 3: Prepare L-CF@HEAs samples by liquid phase laser scanning ablation of the dried foam copper precursor.

2. The method for preparing the laser-modified composite lithium metal battery negative electrode material according to claim 1, characterized in that: The chloride salt in step 1 includes HAuCl4, FeCl3, CoCl2, NiCl2, and CrCl3.

3. The method for preparing the laser-modified composite lithium metal battery negative electrode material according to claim 1, characterized in that: The metal element concentration in step 1 is 0.01 mol / L.

4. The method for preparing the laser-modified composite lithium metal battery negative electrode material according to claim 1, characterized in that: In step 2, vacuum dry for 4-8 hours.

5. The method for preparing the laser-modified composite lithium metal battery negative electrode material according to claim 1, characterized in that: The loading amount of the precursor solution in step 2 is 1-2 mL / cm -2 .

6. The method for preparing the laser-modified composite lithium metal battery negative electrode material according to claim 1, characterized in that: In step 2, dry at room temperature for 4-8 hours.

7. The method for preparing the laser-modified composite lithium metal battery negative electrode material according to claim 1, characterized in that: The conditions for liquid phase laser scanning ablation in step 3 are: laser frequency 20 KHz, scanning speed 600 mm / s, spot diameter 30 μm, galvanometer focal length 11.8 mm, and average power 2 W.

8. A laser-modified composite lithium metal battery negative electrode material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.

9. The laser-modified composite lithium metal battery negative electrode material according to claim 8, characterized in that: The negative electrode material of lithium metal batteries is relatively neat and smooth.

10. The laser-modified composite lithium metal battery negative electrode material according to claim 8, characterized in that: The contact angle between the negative electrode material of lithium metal battery and the electrolyte is 2.5 degrees.

Citation Information

Patent Citations

  • Method for preparing micro-nano medium-entropy and high-entropy materials through laser ablation

    CN112643040A

  • Copper-based current collector and preparation method and application thereof

    CN117039002A

  • CuInNiSnCd high-entropy alloy / carbon fiber composite material and preparation method and application thereof

    CN118287681A

  • Three-Dimensional Architected Pyrolyzed Electrodes for Use in Secondary Batteries and Methods of Making Three-Dimensional Architected Electrodes

    US20190103600A1

  • Laser scanning ablation synthesis of medium-entropy and high-entropy particles with size from nanometer to micrometer

    US20220111466A1

Cited By

  • Laser-etched three-dimensional alloy zinc negative electrode material and preparation method and application thereof

    CN120998947A